A biodegradable multifunctional nanoplatform based on antimonene nanosheets for synergistic cancer phototherapy and dual imaging. Issue 45 (1st November 2021) - Jin, Xiaokang; Xu, Chengfeng; Hu, Jinhua; Yao, Shuting; Hu, Zhiwen; Wang, Bing
Abstract : Schematic diagram for the preparation of AMNS/AuNPs@CS/IR820 formed by antimonene nanosheets (AMNS), gold nanorods (AuNRs), chitosan (CS) and IR820 via electrostatic adsorption for synergistic cancer phototherapy and dual imaging. Abstract : Recently, nanomaterials have been well-studied in cancer therapy, but some of them often experience difficulties with degradation in vivo, which could cause severe damage to the human body. Among numerous biodegradable nanomaterials, antimonene nanosheets (AMNSs) are versatile, and possess photothermal and photodynamic properties and photoacoustic imaging (PAI) and drug loading ability. Herein, we employed a clearable multifunctional system. The small molecule photosensitizer IR820 and the gold nanoparticles (AuNPs) at small sizes of approximately 5 nm were loaded onto AMNSs coated with biodegradable chitosan (CS). This nanoplatform showed excellent photothermal and photodynamic properties, satisfactory degradability and photoacoustic imaging ability, good biocompatibility and effective NIR light triggered intracellular synergistic treatment. It also displayed good fluorescence imaging ability in the experiment of cell uptake. These suggested that this versatile nanoplatform was able to significantly enhance the therapeutic efficiency based on synergistic phototherapy, and could also be applied in fluorescence and photoacoustic dual imaging for integrating diagnosis and treatment.